Cloning and Sequencing of G Protein encoding genes of Balanus improvisus - Amir, Sahiba (My University, 2010)
The barnacle Balanus improvisus is a major fouling organism in Swedish waters. Settling of barnacles onto ship hulls leads to biofouling. Antifouling paints are used to prevent the settlement of the barnacles on ship hulls, but some of these have severe impact on marine ecosystems. G-protein-coupled octopamine receptors of B. improvisus have already been cloned and sequenced. It was discovered that these octopamine receptors are activated by the novel antifouling agent medetomidine, leading to inhibition of the settling process of B. improvisus. Research on B. improvisus has been conducted to provide alternatives to toxic substances such as tributyl tin (TBT), copper metal oxides or organic biocides in marine paints. The knowledge about G proteins of barnacles is very limited. We have cloned and sequenced two G protein subunits;Gαq and Gαs. Cloning of Gαq and Gαs was performed by PCR amplification using sequence information based on ESTs from a B. improvisus cDNA library. cDNA was used as template. The obtained sequences were aligned with lobster Homarus americanus sequence. In Gαq different variants of 5´ ends were found whereas in Gαs different variants at the 3´end are present. Interestingly Gαs in B. improvisus has 165 nucleotides longer open reading frame as compared to the one in H. americanus. This is a first step in the cloning of G-protein subunits of B. improvisus. Functional studies of G-protein with GPCRs will be performed in the future. The enchanced knowledge of G-protein and GPCRs in barnacles will contribute to the development of more specific antifouling paints.
Keywords: Livsvetenskaper; Industriell bioteknik; Life Science; Industrial Biotechnology